Industrial electron accelerators type ILU - Auslender, V.L.; Bryazgin, A.A.; Bezuglov, V.V.; Glagolev, G.B.; Gorbunov, V.A.; Cheskidov, V.G.; Gornakov, I.V.; Faktorovich, B.L.; Kokin, E.N.; Lukin, A.N.; Maksimov, S.A.; Nekhaev, V.E.; et al. (Вопросы атомной науки и техники, 2006)
The paper describes ILU type industrial electron accelerators. Their main parameters, design, principle of action, electron beam extraction devices, wide set of auxiliary equipment for various technological processes and ways of their usage are discussed as well.